Inhalation of Formalin Vapors during Gestation: Effects on Placental Integrity and Fetal Viability in Rats - Mahapatra, Archana; Rana, Jigyasa; Pathak, Satish K.; Ravi, Sanjay Kumar; Kumar, Manish; Kumar, Sarvan (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Formalin, a commonly used preservative and disinfectant, presents significant risks to biological systems, particularly through inhalation exposure. This study aimed to investigate the teratogenic effects of prenatal exposure to formalin vapors on fetal development in Sprague-Dawley rats. Eighteen pregnant rats were divided into three groups: Group I: a control group (no exposure), Group II: a 3-hour exposure group, and Group III: a 6-hour exposure group, Group II and Group III received daily exposure to 10% formalin vapor throughout gestation. The results demonstrated notable developmental impairments in the fetuses and placentas of the exposed groups, including placental discoloration, subcutaneous hematomas, and skin abnormalities in the fetuses. Furthermore, multiple stillborn and poorly developed fetuses were observed, and some placentas were underdeveloped, with no visible fetus associated. These findings highlight the potential teratogenic risks of formalin inhalation during pregnancy, underscoring the need for reassessment of occupational and environmental exposure standards to safeguard maternal and fetal health.